Edukasi Pedoman Isi Piringku Pada Anak Sekolah dalam upaya meningkatkan Pengetahuan Gizi Seimbang Pada Siswa Kelas 4, 5 dan 6 di SDN 005 Lubuk Baja Kota Batam - Siska Pratiwi; Haqqelni Nur Rosyidah; Aprilya Roza Werdani; Desy Desy; Lala Atika (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
The Ministry of Health introduced the “Fill My Plate” program as a daily food guide to achieve good nutritional status. The concept of the contents of my plate visually shows the composition of the food on one plate for one meal. 50% of the contents of the plate in "fill my plate" consists of food sources of energy and builders. Objectives and Benefits of the activity to increase the knowledge of school children and teachers regarding the contents of my plate, increase public awareness in efforts to prevent obesity, as a training tool for nutrition students in providing nutrition and health education to the community. This activity was attended by school children in grades 4, 5 and 6 at SDN 005 Lubuk Baja. The result of this outreach activity is an increase in school children's knowledge regarding balanced nutrition. It is hoped that after counseling children will be able to eat balanced nutritional foods appropriately and adequately so that children can grow normally and not be obese.